Investment and Financing Decisions on Firm Value: The Mediating Effect of Dividend Policy - Sahroni; Sakdiah binti Md Amin; Yulian Bayu Ganar (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to analyze the influence of investment decisions and financing decisions on firm value with dividend policy as a mediating variable in sharia manufacturing companies listed in the Indonesian Sharia Stock Index. The research method uses a quantitative approach with Partial Least Squares-Structural Equation Modeling analysis. Data were obtained from the financial statements of sharia manufacturing companies during a certain observation period and processed using SmartPLS software. The results show that investment decisions have a positive and significant effect on both firm value and dividend policy. Financing decisions are also proven to have a positive effect on both firm value and dividend policy. Furthermore, dividend policy has a significant effect on firm value, confirming its role as a signal for investors. In addition, dividend policy is proven to mediate the relationship between investment decisions and financing decisions on firm value, thus strengthening the indirect influence mechanism in increasing firm value. These findings contribute to the development of financial management theory, particularly in the context of sharia manufacturing companies, and provide practical implications for management in formulating optimal financial strategies to increase firm value.